EKSISTENSI ORANG TUA DALAM KUMPULAN CERPEN ROBOHNYA SURAU KAMI KARYA A.A. NAVIS: PENDEKATAN PSIKOLOGI SASTRA - Ariyadih (Scientia Integritas Utama, 2022)
In a story, each character has a different existence or role. With this difference, problems arise in each character, one of which is the parent character. The purpose of this study is to find out the intrinsic elements and how the problems of the existence of parents in the three collections of short stories Robohnya Surau Kami, the three short stories the author chose, namely Anak Kebanggaan, Nasihat-nasihat, and Datangnya dan Perginya with a literary psychology approach. To analyze the data, the researcher used a qualitative descriptive method. The qualitative descriptive method analyzes objects, and the results are described in the form of descriptions. The researcher uses objects from the problems faced by parents in three short stories. This study's data sources were the short stories Anak Kebanggaan, Nasihat-nasihat, and Datangnya dan Perginya of the short stories The Collapse of Surau Kami by A.A. Navis. The stages in analyzing this research data use qualitative analysis, according to Miles & Huberman. This research can find out the problems in the three short stories about the existence of parents, namely, about giving meaning to their children, parents' choices in living the next life, losing a wife or mother, parental anxiety, parental guilt to the child and the free will of the parents.